Sikkim State Annual Plan 2002-2003 Planning and Development Department Government of Sikkim Gangtok - Planning Commission (Planning Commission, 2002)
Sikkim is a small Indian State in the eastern Himalaya, lying between 270 04’46"" and 280 07’48"" north latitude and 880 58” and 880 55’25” east longitude. It is a unique mountainous state encircled by three different international boundaries. To its west lies Nepal, Bhutan and the Chumbi Valley of the Tibetan Autonomous Region, the people’s Republic of China in the east, Darjeeling Gorkha Hill Council of West Bengal, in the south, and the Tibetan Plateau of the Tibetan Autonomous Region, the People’s Republic of China in the north. It extends approximately 114 Km from north to south and 64 Km from east to west with altitude ranging from 300 to 8598 mas having 447 villages comprising mainly three ethnic groups namely Lepchas, Bhutias and Nepalese. Mount Khangchendzonga located in Sikkim is the third tallest mountain in the world. Sikkim is a part of upper Teesta basin. the main tributary of the Teesta river is the Great Rangit river.
Planning and Development Department Government of Sikkim Gangtok